Design A Wideband (25-40ghz) Mm-Wave Microstrip Antenna for 5g Applications - Azizan, Syakir Syahiran; Al-Fadhali, Najib Mohammed Ahmed; Huda Majid; MSM Gismalla; Jameel A. A. Mukred; Adel Y.I. Ashyap; B.A.F Ismail; N. A. M. Alduais (Progress in Engineering Application and Technology, 2021)
Millimeter wave is the spectrum between microwaves and infrared waves that is commonly known as extremely high frequencies, which is suitable for 5G networks. Features like as antenna size, bandwidth, power consumption, traffic demand, and a high rate of data increase the need for such an antenna design. The aim of this research is to design wideband Mm-Wave microstrip patch antenna for 5G application system. The design consists of edge-cut approach, an Inset-fed rectangular patch antenna with partial ground. The proposed antenna can cover the 5G application from range (25 GHz – 40 GHz). The simulated result of bandwidth, return loss and VSWR shows the capability of the antenna that suits for 5G Mm-Wave application systems. This proved that proposed antenna can obtain wide bandwidth and high return loss by using four edge slots at the patch with partial ground. The Modified Inset-fed MPA demonstrates that this antenna is ideal for 5G Mm-Wave application.